Hidrogeoquímica e estado trófico de reservatório do semiárido brasileiro sob a influência de estiagem prolongada. - Santos, Janaína Andrade dos (2016)
Global climate change will have a strong impact on the hydrological cycle and water resources of the semiarid regions. The multiple use of water will require an integrated approach to understand the physical, chemical and biological effects of climate on water resources. The development of scientific research makes relevant the quantifying of the forcings that alter the biogeochemical cycling and water quality of the reservoirs. The Castanhão reservoir recorded a dramatic decrease in volume, providing a unique opportunity to understand the relationship between volume, the trophic state and the influence of anthropogenic pressures. Thus, the objective of this study was to investigate the influence of changes in climate and anthropogenic conditions on patterns of interannual and spatial heterogeneity of Castanhão reservoir’s limnological variables. Between November 2011 and May 2014 water samples were taken at four depths of the water column. Data were obtained in situ of pH (6.1 to 9.9), conductivity (287-372 μS/cm) Turbidity (0.7 to 4.2 NTU), dissolved oxygen (0.1 - 11 7 mg/L) and temperature (27.1 to 32.6 °C). In laboratory it was carried out the analysis of total phosphorus, soluble reactive phosphorus, total nitrogen, nitrate, nitrite, ammonia nitrogen and chlorophyll-a ranging from 5.4 to 158 µg/L, 2.5 to 114.5 µg/L, 97.6 to 1209.9 µg/L, 33 to 105.8 µg/L, 0.3 to 35.4 µg/L, 19.8 - 384.9 µg/L and 0.9 to 42.3 µg/L, respectively. The trophic state index ranged from oligotrophic to eutrophic. Sediment samples indicated total phosphorus values ranging between 70 and 270 µg/g. The total inorganic phosphorus was the dominant fraction. The prolonged drought caused a drastic decrease in the volume of the reservoir, leading to changes in the physical structure, chemical and biological system: Eutrophication processes are not uniformly distributed throughout the reservoir, affecting the formation of different compartments. The thermal structure of the water column was determined by climatic and morphometric factors that interfere in the dynamics of oxygen, chlorophyll and nutrients. Anoxic events occurred in the hypolimnion, indicating that eutrophication processes are occurring. Higher nutrient concentrations were found in the hypolimnion. The action of the winds may have broken the stability of the water column and favored the processes of mixing and resuspension of sediment. Thus, global climate change scenario should be taken into consideration in the management of multiple uses of the Castanhão reservoir in order to ensure sustainability and nobler uses. Reduction in rainfall and increased frequency of extreme events in the semiarid region, prolonged droughts and heavy rains could increase the eutrophication processes in Castanhão reservoir.